2021
DOI: 10.1080/09658211.2021.1995876
|View full text |Cite
|
Sign up to set email alerts
|

To mention or not to mention? The inclusion of self-reported most traumatic and most positive memories in the life story

Abstract: Many theories on Posttraumatic Stress Disorder (PTSD) make assumptions on the relationship between PTSD and centrality of traumas to the life story and identity. Although the Centrality of Event Scale (CES; Berntsen & Rubin, 2006) is a popular measure of centrality of personally experienced events to the life story, no studies have examined whether self-rated "central" events are mentioned, when individuals recount their lives. It is also unknown if mentioning specific event types in the life story is related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Thus, the current study may not have been able to detect age-group differences in event centrality simply because too few participants considered the event central to their life stories. Previous research have found natural disasters to be relatively weakly associated with PTSD compared to other trauma types (Darves-Bornoz et al, 2008;Kessler et al, 1995), just as accident and disaster type traumas have been found to be less likely to be included in life stories (Kongshøj et al, 2022). Thus, to test whether young adults consider traumas as more central to their life story than other adults do, future research should focus on participants who are victims of trauma types known to be highly related to PTSD.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
“…Thus, the current study may not have been able to detect age-group differences in event centrality simply because too few participants considered the event central to their life stories. Previous research have found natural disasters to be relatively weakly associated with PTSD compared to other trauma types (Darves-Bornoz et al, 2008;Kessler et al, 1995), just as accident and disaster type traumas have been found to be less likely to be included in life stories (Kongshøj et al, 2022). Thus, to test whether young adults consider traumas as more central to their life story than other adults do, future research should focus on participants who are victims of trauma types known to be highly related to PTSD.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
“…The present study is based on parts of the dataset employed in Kongshøj et al (2021), and participants and methods between the two articles are partially overlapping. Participants were recruited from Amazon Mechanical Turk (MTurk) through the Cloud Research platform (Litman et al, 2017).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Participants were recruited from Amazon Mechanical Turk (MTurk) through the Cloud Research platform (Litman et al, 2017). Participants in the present study took part in a larger survey with a total of 386 native English-speaking participants (see Kongshøj et al, 2021, for details on the larger survey sample). In the present study, only participants whose most traumatic event happened when they were 14-25 years old (hereafter referred to as "youth trauma group"), and participants whose most traumatic event happened after they turned 30 (hereafter referred to as "adult trauma group") were included.…”
Section: Methods Participantsmentioning
confidence: 99%
See 2 more Smart Citations